Identifying canopy architecture traits to optimize light and increase radiation-use efficiency and grain yield in wheat - Moroyoqui Parra, Marcela Alejandra (2022)
Wheat is the most widely grown crop which produces ~766 million tonnes per year (FAOSTAT, 2019) supplying 20% of the calories and protein for the human population (Braun et al., 2010). Staple crops (wheat, maize, rice and soybean) must increase their yield by 2.4% per year to meet the food demand for a growing population (Ray et al., 2013). Climate change has been predicted to increase the global temperature by ~ 2-4°C by the end of the 21th century (IPCC, 2014), with more frequent flooding and drought decreasing the production of grain crops (IPCC, 2014; Asseng et al., 2015). Harvest index (grain dry matter as a proportion of above-ground dry matter; HI) is approaching its theoretical limit (Austin et al., 1980; Foulkes et al., 2011), so other alternatives must be explored to increase biomass and hence grain yield. Radiation-use efficiency (above-ground dry matter per unit radiation interception; RUE) has therefore become an important trait for raising biomass and grain yield potential in plant breeding (Foulkes and Murchie, 2011a). In recent decades, growers in the Northwest of Mexico have adopted a raised-bed planting system (Fahong et al., 2004). This planting system showed advantages compared to the traditional flat-basin planting system such as water savings and reduced weeds and diseases (Fahong et al., 2004). However, effects on grain yield are still inconsistent so further studies are needed to prove grain yield benefits.